Exploring Management Food and Beverage Students' Perception and Expectation of Using Presentation and Dialogue in English Language Learning - Agung Rai Antara, I Made; Yunik Anggreni, Ni Putu (Jurnal Manajemen Pelayanan Hotel, 2023)
This study aims to analyze Diploma III Management Food and Beverage students’ perception and expectation regarding the use of dialogue and presentation in English Language Learning in Faculty of Tourism, Triatma Mulya University. The sample used was 6 Students of Management Food and Beverage. The methods used to collect data was deep interviews to analyze their perceptions and expectations about the use of dialog and presentation. In addition to this, the supporting data was collected through online publications. The research shows that most of the students’ opinions are positive. Students think that those two techniques can help them to improve their English skills, especially speaking and listening. They feel more confident speaking English because they are provided activities where they must speak in front of their friends and receive feedback from teachers and friends which makes them know how to do better in the next meeting. In terms of expectations, students expect that these two methods can improve their self-confidence and expand their English. They hope that after studying English at University, they will have better preparation to work in the industry. They think through these methods they can improve their public speaking so that they can be professional workers. They consider that presentation and dialogue can enrich their vocabulary and grammatical structure. Even though in the classroom each student has a different level of English. They conclude that they have the same expectation, which is to have better English. Keywords: Dialogue, Presentations, Perception, Expectation